An Exploratory Analysis of the Speech Act of Apology and its Associated Sociocultural Factors - Fuentes-Mascuñana, Evelyn (Silliman Journal, 2022)
LANGUAGE is part of social life; in fact, they are interdependent. Through language, culture becomes part of individual and group experience. Through daily social interaction, linguistic aspects of social structure, cultural values and beliefs in turn become inter-nalized. One important means of studying the social roles, status, structure of a community, therefore, would be to study its speech behavior (Hymes 1964: 215). To efficiently describe speech behavior and its linguistic forms one needs to have a restricted focus. Hymes's (1972) pro-posed distinction of speech situation, speech event, and speech act is a useful framework for such a purpose. His framework provides a hi-erarchy with the speech situation at the top and speech act at the bottom. (See also Olshtain and Cohen 1983: 19). The speech situation has the broadest scope and Hymes pos-its that one finds many speech situations within a speech commu-nity such as meals, parties, conferences, and auctions which in themselves are not governed by consistent rules. The speech event takes place within the speech situation and, unlike it, is restricted to activities that are directly governed by rules of speech—e.g., lectures, introductions, advertising, and two or more party conver-sations. The speech act has the narrowest scope and is the minimal term on the scale. It refers to the acts we perform when we speak. As such, it is defined in terms of discourse function. Speech acts can still be further restricted. The Speech Act Theory of John Searle is valuable in delimiting the study of speech behavior suggested at the beginning of the paper. It is also useful in coming up with a narrower and more efficient theoretical frame-work within which to describe and analyze it. A brief background of the theory can give us a picture of the topic under discussion. Austin (1962, 1971) asserts that an utterance is also the doing of some action, that speech is accomplishing something with words. In uttering "The courtroom is quiet," one describes, but in saying "I promise to come," oPe is doing the act of promising. Such utterances are called performative utterances and their verbs perfor-matives (See also Malmkjaer 1991: 416). Speech Act of Apology • 7 John Searle, one of Austin's students, extended Austin's ideas in his work Speech Acts in 1969. His fundamental assumption is that all utterances constitute acts, not just those containing per-formative verbs. According to his Speech Act theory, every time we direct language at some audience we perform three simultane-ous acts. The locutionary act is the act of simply uttering a sentence from a language. It is a description of what the speaker says and is composed of a referring expression (e.g., a noun phrase) and a predi-cating expression (e.g., a verb phrase or adjective). "The vacation is over" has the referring expression the vacation and the predicating expression is over. The illocutionary act is what the speaker intends to do by an utterance. They include requesting, apologizing, promising, pre-dicting, ordering, threatening, and stating. "Submit your work at the end of the week" spoken by a teacher to her student is an act of ordering. The intent associated with an illocutionary act is called the illocutionary force. The perlocutionary act is the effect on the hearer of what a speaker says. They include inspiring, irritating, persuading, embar-rassing, intimidating, or boring the hearer. The illocutionary act of "You'd better study for the exam" might be one of urging but when spoken by a teacher to a student in front of the entire class, the perlocutionary act is one of threatening or embarrassing (Searle 1971; Parker 1986).